(untitled) (Revista de Ciências Agroveterinárias, 2025)
The application of molecular markers in beef production has garnered significant attention in recent years due to its potential to enhance productivity and efficiency. This study conducted a systematic review and bibliometric analysis using the Web of Science (WoS) database to identify and analyze the main molecular markers utilized in beef production. A total of 808 articles published between 2013 and 2023 were retrieved, of which 722 met the inclusion criteria after duplicate removal and filtering by publication year. The bibliometric analysis was performed using the R software and the bibliometrix R package to examine keyword trends and research patterns. The results indicate that Single Nucleotide Polymorphisms (SNPs) and Polymerase Chain Reaction (PCR) were the most frequently cited molecular markers, highlighting their relevance in genetic improvement studies. PCR remains the most widely used technique due to its efficiency in DNA amplification, while SNPs offer a high-resolution approach to detecting genetic variations. Conversely, Amplified Fragment Length Polymorphism (AFLP) marker was the least cited, likely due to its labor-intensive and cost-prohibitive nature. A geographical analysis of the publications revealed that China, the United States, and Brazil were the leading contributors, with China emerging as the most prolific country in this field. Despite being one of the largest beef producers, Brazil lags in scientific contributions, primarily due to limited research funding. The findings indicate an increasing integration of molecular markers in beef production. However, a knowledge gap persists in connecting genetic markers with microbial resistance and meat quality traits. Future research should address these connections to optimize meat production efficiency and quality.